IN-DEPTH INVESTIGATION OF VARIATIONS IN RISER QUANTITY USING EXPENDABLE MOLDS - Riyanto, Obaja Eden Sentosa; J, Khansa Farrel; I.Y.H, Kyagus Ahmad; E., Wahyu Dwi; Akbar, Rafi; Lubis, Didin Zakariya (Department of Mechanical Engineering Education, 2024)
This study explores and investigates the impact of the riser quantity on shrinkage and surface quality of two cast products in the sandcasting process. The research was conducted in several stages: preparing the mold and equipment, performing the casting process, investigating shrinkage, and inspecting the products using a macro camera. Experimental results demonstrated that the number of risers significantly influences the final product quality. Specifically, the average shrinkage for molds with one riser was found to be 3.18% and 5.01% for the first and second products, respectively. In comparison to molds with two risers presented decreased shrinkage, with averages of 0.9% and 2.06% for the first and second product, respectively. Additionally, defects investigated and observed in the first product with a single riser mold underscore the importance of riser quantity alongside casting parameters. The findings of this research highlight that increasing the number of risers can enhance casting quality by minimizing shrinkage. improving surface finish. This research presented essential insights for optimizing riser design and quantity for expendable mold in sandcasting technology to achieve superior cast products quality.